The Effect Of Human Resources Development Andorganizational Culture On Employee Performance At The Office Of DPMPTSP, Lebong Regency - Yanti, Meili; Susanti, Neri; Rahman, Abdul (Utami Publisher, 2024)
The purpose of this study was to determine the effect of Human Resource Development and organizational culture on employee performance at the Lebong Regency DPMPTSP Office. The sample in this study was 46 employees at the Lebong Regency DPMPTSP Office. The data was collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 7.828 + 0.386X1 + 0.445 X2, this describes a positive regression direction, meaning that there is a positive influence between X1 (HR development) and X2 (organizational culture) on performance (Y). It means that if the variables of HR development and organizational culture increase, it will increase performance. The value of the coefficient of determination is 0.557. This means that X1 (HR development) and X2 (organizational culture) affect performance (Y) by 55.7% while the remaining 44.3% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explain that partially the variables of HR development and organizational culture have a significant influence on employee performance variables at the Lebong Regency DPMPTSP Office. The results of the F test at a significance level of 0.05 explain that the variables of HR development and organizational culture have a significant simultaneous influence on employee performance at the Lebong Regency DPMPTSP Office.